GRUP NOMINA KOMPLEKS PADA NOVEL LORD OF THE RINGS KARYA J. R. R. TOLKIEN - Puspahaty, Novita (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2013)
This research is entitled Nomina Group Complexes in English: A Func-tional and Transformational grammar approach. This research discusses: 1) what groups usually appear on nomina group complexes based on functional grammar approach and 2) what phrase usually appear on nomina group com-plexes based on transformational grammar approach. This research method used is descriptive method which employs classification of groups, and nomi-na group complexes. This research, employs theory of M.A.K Halliday for functional grammar approach and Chomsky?s theory for transformational grammar approach. The result of this research shows that: 1) Group usually appear on nomina group complexes based on functional grammar approach is only prepositional group, 2) Groups usually apear on nomina group complexes based on transformational approach are adjetive phrase and prepositional phrase.